Optimal Redistribution in the Presence of Signaling - Spencer Bastani; Tomer Blumkin; Luca Micheletto (Center for Economic Studies and ifo Institute (CESifo), 2021)
We analyze optimal redistribution in the presence of labor market signaling where innate productive ability is not only unobserved by the government, but also by prospective employers. Signaling in both one and two dimensions is considered, where in the latter case firms have an informational advantage vis-a-vis the government. The dual role of income taxation in redistributing income and affecting signalling incentives is analyzed, as well as extended tax systems that combine income taxation with direct instruments allowing the signals to be taxed. A key focus is the analysis of the feasibility and social desirability of redistribution through wage compression.
Keywords: D82; H21; H52; J31; 330; optimal taxation; signaling; education; monitoring